Breaking the Barriers to Higher Economic Growth : Better Governance and Deeper Reforms in the Middle East and North Africa - Nabli, Mustapha Kamel (Washington, DC: World Bank, 2012)
Contents of the report are as follows: Long-term economic development: challenges and prospects for the Arab countries by Mustapha K. Nabli. Reform complementarities and economic growth in the Middle East and North Africa by Mustapha Kamel Nabli, and Marie-Ange Veganzones-Varoudakis. After Argentina: was MENA right to be cautious? By Mustapha K. Nabli. Restarting Arab economic reform by Mustapha K. Nabli. Democracy for better governance and higher economic growth in the MENA region? By Mustapha K. Nabli, and Carlos Silva-Jauregui. The political economy of industrial policy in the Middle East and North Africa by Mustapha K. Nabli, Jennifer Keller, Claudia Nassif, and Carlos Silva-Jauregui. The macroeconomics of labor market outcomes in MENA by Jennifer Keller, and Mustapha K. Nabli. Challenges and opportunities for the 21st century by Mustapha Nabli. Labor market reforms, growth, and unemployment in labor-exporting countries in the Middle East and North Africa by Pierre-Richard Agenor, Mustapha K. Nabli, Tarik Yousef, and Henning Tarp Jensen. Economic reforms and people mobility for a more effective EU-MED partnership by Ishac Diwan, Mustapha Nabli, Adama Coulibaly, and Sara Johansson de Silva. Cruise control, shock absorbers, and traffic lights by Mustapha K. Nabli. Trade, foreign direct investment, and development in the Middle East and North Africa by Farrukh Iqbal, and Mustapha Kamel Nabli. Making trade work for jobs by Dipak Dasgupta, Mustapha Kamel Nabli, Christopher Pissarides, and Aristomene Varoudakis. Exchange rate management within the Middle East and North Africa region by Mustapha Nabli, Jennifer Keller, and Marie-Ange Véganzones. How does exchange rate policy affect manufactured exports in MENA countries? By Mustapha Kamel Nabli, and Marie-Ange Veganzones-Varoudakis. Public infrastructure and private investment in the Middle East and North Africa by Pierre-Richard Agenor, Mustapha K. Nabli, and Tarik M. Yousef. Governance, institutions, and private investment by Ahmet Faruk Aysan, Mustapha Kamel Nabli, and Marie-Ange Veganzones-Varoudakis.